THE ROLE AND IMPORTANCE OF GEOMORPHOLOGICAL FACTORS IN THE EMERGENCE AND DEVELOPMENT OF THE CITY OF ERSHI (Scientific journal of the Fergana State University, 2024)
This article examines the long-term preservation and development of settlements that arose in areas with favorable geographical conditions and whose residents rationally used this opportunity. If cities were destroyed under the influence of anthropogenic factors (as a result of wars), they were rebuilt in a favorable geographical position. This situation is analyzed using the example of the Ershi settlement (the area of the historical monument Mingtepa, Markhamat district, Andijan region). The natural, economic, transport and military-geographical position that influenced the formation and development of the city of Ershi is analyzed.